Study Social Media Interconnectedness To Strategy Marketing with Internal Language Dimensions Smart Heritage Market Context : A Study Badung Market Case - Rinayanthi, Ni Made (Jurnal Manajemen Pelayanan Hotel, 2024)
Study This aim For investigate connection between strategy marketing and dimensions Language in legacy market context smart (Smart Heritage Market), with focus on the Badung Market Case . In context globalization , legacy markets like Badung Market face challenge For still relevant and competitive in the digital era. One of aspect important from legacy market transformation being “smart” is use strategy effective marketing that leverages riches culture and history of the market . Beside that , language also holds role key in build market identity , communicating values legacy , and interesting interest consumer . Studies This use approach qualitative with interview depth and observation to practice marketing and use language at Badung Market . Analysis results show that strategy successful marketing in legacy markets must consider context culture and history local , as well utilise digital technology with wise . Use proper language , fine in promotion nor interaction direct with customers , too factor important in build connection emotional and empowering market image . Study This give contribute to understanding about How strategy marketing and dimensions Language each other influence in legacy market context clever . Implications practically including recommendation for holder heritage market interests For develop strategy more marketing effective and language - based , as well utilise potency technology For increase experience consumers and promote inheritance culture in a way sustainable . Keywords : Language Dimensions , Strategy Marketing , Smart Heritage Market, Badung Market